لماذا تتوزَّع كفاءة المترجم بشكلٍ متغايرٍ بين الأشخاص المثقّفين لغوياً؟ (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2016)
This piece of research endeavours to explain why translator's competence is not homogeneously distributed among linguistically acculturated members of society. It transpires that the cross-cultural communication skills possessed by a translator are not often born or merely characteristics of his natural ability. Professional translation is an evolved natural translation. Undoubtedly, it is training, deepened expertise, and constant upgraded and updated cognizance of the technicalities and strategies of translation that qualify a translator to overcome the ever arising problems of translation. The cognitive activity of translator's communicative competence underlies his professionalism concerning the issues of invisibility, interference, creative restructuring process of problem-solving and decision-making. Quite contrasted to translator as transmitter, accumulative malleable communicative competence creates the translator who is a genuine cultural mediator.يحاول هذا البحث إيضاح ماهية عدم توزّع كفاءة المترجم بشكلٍ متجانسٍ بين أفراد المجتمع المثقّفين لغوياً. من الجليّ أنّ مهارات التخاطب عبر الثّقافات والتي يمتلكها المترجم ليست على الغالب مولودةً أو أنّها مجرّد خصائص لمقدرته الطبيعية. فالتّرجمة الحِرفية ترجمةٌ طبيعية متطوّرة. إنّه التّدريب، دون شكّ، والخبرة المعمَّقة، والإلمام المباشر المحدَّث والمطَوّر لتقنيات واستراتيجيات الترجمة والتي تخوّل المترجم التّغلّب على مشاكل التّرجمة المستدامة الظهور. والنّشاط المكتسب لكفاءة المترجم التّخاطبية يشكّل الأساس لحِرَفيته فيما يخصّ مسائل البطون، والتّدخّل وعمليات إعادة البناء الخلاّقة المتمثّلة في حلّ المشاكل وصناعة القّرار. وبشكلّ مغاير للمترجم النّاقل، فإنّ كفاءة المترجم التّخاطبية المرِنة والتّراكمية تخلق المترجم الذي يُعدُّ وسيطاً ثقافياً حقيقياً.